Performance Evaluation of Pelton Turbine: A Review - Gupta, Vishal; Khare, Ruchi; Prasad, Vishnu (Hydro Nepal: Journal of Water, Energy and Environment, 2014)
Earlier only experimental techniques were used to predict the performance of turbines. With advanced numerical techniques and increase in processing power of computers, Computational Fluid Dynamics (CFD) has emerged as an effective tool for the performance prediction of Pelton hydraulic turbine involving multi-fluid flow. Extensive work has been done for design optimization of reaction turbines using CFD. Now it is being extended for impulse turbines. The flow in reaction turbines involves only water as working medium, but in case of impulse turbines, water and air are working medium. The water jet issued from nozzle is surrounded by air and pressure around the jet and turbine is atmospheric. The performance of Pelton turbine depends upon the shape, size and quality of jet as well as shape of the buckets. In the present paper, the literature review on applications of CFD for performance prediction, design optimization of Pelton turbine have been discussed. DOI: http://dx.doi.org/10.3126/hn.v13i0.10042 HYDRO NEPAL Journal of Water, Energy and Environment Issue No. 13, July 2013 Page: 28-35 Uploaded date: 3/13/2014